Two-directional synthesis and biological evaluation of alkaloid 5-epi-cis-275B′ - Procopiou, George; Aggarwal, Pooja; Newton, Annabella F.; Richards, David; Mellor, Ian R.; Harbottle, Gareth; Stockman, Robert A. (Royal Society of Chemistry, 2014)
The first total synthesis of myrmicine ant alkaloid 5-epi-cis-275B0 (4) is presented. A tandem cyclisation stablished the entire core of the structure in a single transformation as well as the required 2,5-anti stereochemistry. Two-directional synthesis was used to furnish the cyclisation precursor 2, as in each of the subsequent steps towards the natural product. The first electrophysiology studies for 4 (against nicotinic acetylcholine receptors) were also conducted, finding modest inhibition of current.